15N isoscapes in a subtropical savanna parkland: spatial‐temporal perspectives. Issue 1 (11th January 2013) - Bai, Edith; Boutton, Thomas W.; Liu, Feng; Wu, X. Ben; Archer, Steven R.
Abstract : Spatial patterns of soil δ 15 N reflect variation in rates of N‐cycling processes across landscapes. However, the manner in which soil δ 15 N is affected by vegetation and topoedaphic properties under non‐steady state conditions is understood poorly. Here we propose and evaluate a conceptual model that explains how soil δ 15 N values will respond to changes in disturbance regimes (intensification of grazing and removal of fire) and the resultant invasion of a subtropical grassland by woody vegetation dominated by Prosopis glandulosa (honey mesquite), a N‐fixing tree legume. Spatially‐specific sampling along a catena (hill‐slope) gradient where woody plants are known to have displaced grasses over the past 100 years revealed a positive relationship between soil δ 15 N and δ 13 C, and a negative relationship between NDVI and soil δ 15 N on upland portions of the landscape, indicating that plant cover is a critical determinant of δ 15 N spatial patterns. Because the dominant woody invader is a N‐fixer, its invasion has increased N input and reduced soil δ 15 N. However, while honey mesquite also invaded and came to dominate lowland portions of the landscape, soil δ 15 N values in woodlands of intermittent drainages were significantly elevated relative to those in uplands. This is likely attributable to higher soil moisture, clay content, and total N in the lower portions of the catena gradient, which create conditions favoring more rapid N‐transformation rates, higher preferential 14 N losses (e.g., gaseous), and thus enrichment of 15 N. Thus, while spatial and temporal variation of soil δ 15 N has the potential to be an indicator of disturbance‐induced changes in the net N balance, its sensitivity is compromised in topoedaphic settings with where rates of N‐transformation are high. Continued improvements in our understanding of controls over the spatial variability of soil δ 15 N at the landscape‐scale will enhance our ability to use δ 15 N as a diagnostic tool for inferring N dynamics under both steady‐state and disturbed conditions.